Composite material containing oxygen vacancies as well as preparation method and application of composite material
By mixing metal salts, biomass raw materials and etchants in the presence of solvents, carbonizing invading plants, forming oxygen-containing vacancies composite materials and combining them with persulfate, the existing biochar catalysts are solved. The low efficiency of removing organic pollutants in water bodies is solved. Problem, efficient depth removal is achieved.
Patent Information
- Application Number
- CN202310787683.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
When removing organic pollutants in water, the existing biochar catalysts have low removal rates and mineralization rates, making it difficult to achieve deep removal, and the electron conduction rate is poor, which limits its application.
Using an oxygen-containing vacancies, the carbonized biomass raw materials are mixed with metal salts, biomass raw materials, accelerators and etchants in the presence of solvents, and invasive plants are selected as raw materials, and the transition metal salts are combined to improve the Catalytic properties and combined with persulfate to form an efficient catalytic system.
It has achieved efficient removal of various organic pollutants in water bodies, with a removal rate of 100% and a mineralization rate of 80%, significantly improving the efficiency and stability of the catalyst.
Smart Images

Figure CN119215914A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a composite material containing oxygen vacancies and a preparation method and application thereof. Background Art
[0002] Biochar is a solid product obtained by high-temperature pyrolysis of biomass under anaerobic or anaerobic conditions. After the pyrolysis and carbonization of biomass, biochar becomes a microporous structure with rich pore structure, large specific surface area and small bulk density. In recent years, it has gradually become a research hotspot in the fields of agriculture, ecological restoration and environmental protection.
[0003] At present, the raw materials for synthesizing biochar are mainly crop straw (such as wheat, cotton, corn, etc.), fallen leaves, kitchen waste, livestock and poultry manure (such as chicken manure, pig manure, cow manure, etc.) and sludge. The performance of biochar is closely related to the properties of the raw materials and the carbonization process. The organizational structure, inclusions, lignin and cellulose content of different biomasses are different, and the structure of the prepared biochar is significantly different. For example, the total nanopore size of biochar prepared from rice husks is 2.1cm 3 ·g -1 , while the sludge biochar is 0.17cm 3 ·g -1 .
[0004] At present, the research on biochar mainly focuses on using biochar to replace expensive activated carbon as a catalyst or carrier to treat wastewater, waste gas and promote lipid synthesis. However, the existing biochar can only achieve the adsorption of pollutants, and its electron conduction rate is poor. The disordered carbon structure cannot achieve effective directional transfer of electrons, which limits the practical application of biochar in the field of catalytic removal of pollutants. Therefore, researchers also need to improve the performance of biochar and transform it into an advanced composite material with new structure and surface properties in order to maximize its catalytic efficiency and stability. Compared with the original biochar, the transition metal loading modification method changes the electronic state of biochar, making its derivatives more electrophilic, further improving the ability and application of biochar-based materials as catalysts to remove pollutants in water. However, the catalysts prepared by using loaded metal modified biochar have the following main defects: 1) The active sites are not fully exposed, which reduces the contact opportunity between the reactants and the active sites; 2) The loaded metal modified biochar catalyst has poor conductivity, which increases the resistance to electron transfer during the catalytic process, resulting in the catalyst's adsorption capacity and activity are still poor. When used to degrade organic pollutants in water, the organic pollutants have a long degradation time, low removal rate, low mineralization rate, and difficulty in deep removal.
[0005] Therefore, it is necessary to seek a new composite material containing oxygen vacancies and its preparation method, while improving the ability of the composite material to degrade organic pollutants in water, improve the mineralization efficiency, and achieve deep removal. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of low removal rate and mineralization rate of organic pollutants in water bodies and difficulty in deep removal of organic pollutants in the catalyst / persulfate activation system in the prior art, and to provide a composite material containing oxygen vacancies and a preparation method and application thereof. The composite material prepared by the present invention can efficiently remove a variety of organic pollutants in water bodies.
[0007] In order to achieve the above object, the present invention provides a method for preparing a composite material containing oxygen vacancies, the method comprising: mixing a metal salt, a biomass raw material, a promoter and an etchant in the presence of a solvent to carbonize the biomass raw material;
[0008] Wherein, the biomass raw materials are derived from invasive plants.
[0009] The second aspect of the present invention provides a composite material containing oxygen vacancies prepared by the method described in the first aspect.
[0010] The third aspect of the present invention provides the use of the composite material containing oxygen vacancies described in the second aspect and persulfate in the degradation of organic pollutants.
[0011] Compared with the prior art, the present invention has at least the following beneficial effects:
[0012] (1) The preparation method of the composite material of the present invention is simple and easy to operate;
[0013] (2) The raw materials used in the present invention are green and environmentally friendly, and can also achieve waste utilization;
[0014] (3) The composite material coupled with persulfate of the present invention can effectively remove various organic pollutants in water, with a removal rate of 100% and a mineralization rate of 80%. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a sample picture of the molybdenum-cobalt bimetallic-Pleurotus eryngii biochar composite material prepared in Example 1.
[0016] Figure 2 This is a scanning electron microscope image of the molybdenum-cobalt bimetallic-Pleurotus eryngii biochar composite material prepared in Example 1.
[0017] Figure 3 This is a transmission electron microscope image of the molybdenum-cobalt bimetallic-Pleurotus eryngii biochar composite material prepared in Example 1.
[0018] Figure 4 3 are electron spin resonance images of the composite materials prepared in Example 1, Example 4 and Comparative Example 3.
[0019] Figure 5This is a scanning electron microscope image of the molybdenum-iron bimetallic-Aster tataricus biochar composite material prepared in Example 2.
[0020] Figure 6 This is a transmission electron microscope image of the molybdenum-iron bimetallic-Aster tataricus biochar composite material prepared in Example 2.
[0021] Figure 7 This is a transmission electron microscope image of the iron-cobalt bimetallic-Alternanthera philoxeroides biochar composite material prepared in Example 3.
[0022] Figure 8 It is a comparison chart of the degradation effects of iohexol by the composite materials prepared in Example 1, Example 2, Example 3 and Comparative Examples 1-2.
[0023] Fig. 9 It is a comparison chart of the degradation effects of iohexol by the composite materials prepared in Example 1, Example 4 and Comparative Example 3. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The first aspect of the present invention provides a method for preparing a composite material containing oxygen vacancies, the method comprising: mixing a metal salt, a biomass raw material, a promoter and an etchant in the presence of a solvent to carbonize the biomass raw material;
[0026] Wherein, the biomass raw materials are derived from invasive plants.
[0027] According to some embodiments of the present invention, the weight ratio of the metal element in the metal salt to the dry matter of the biomass raw material is 1:(0.5-10), such as 1:0.5, 1:1, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6:1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, or any value between the above values or a range consisting of any two values.
[0028] According to some embodiments of the present invention, the invasive plant is a foreign species not native to China, and can be selected from invasive herbaceous plants, in particular, plants of the genus Erigeron and / or plants of the genus Aster of the family Aster. More preferably, the invasive plant is selected from at least one of Erigeron spp., Aster spp. and Alternanthera philoxeroides.
[0029] According to some embodiments of the present invention, the cellulose content in the invasive plant is 45-65 wt % based on the dry matter weight of the invasive plant.
[0030] According to the present invention, the invasive plants are mixed with other raw materials in the form of dry powder.
[0031] In the present invention, when the invasive plants meet the above range, they can be combined with metal salts in a hydrothermal reactor under low temperature conditions to generate a biochar composite material with high stability, less metal element leaching, and reduced energy consumption and secondary pollution.
[0032] In the present invention, the metal salt is preferably a transition metal salt, more preferably at least one of a VIB group metal salt, a VIIB group metal salt and a VIIIB group metal salt. According to some embodiments of the present invention, the transition metal salt is selected from any two of iron salts, molybdates, cobalt salts, copper salts and manganese salts; more preferably, the transition metal salt is selected from any two of iron salts, molybdates and cobalt salts.
[0033] In the present invention, the metal salt is selected from water-soluble metal salts, preferably water-soluble transition metal salts, more preferably at least one of water-soluble Group VIB metal salts, water-soluble Group VIIB metal salts and water-soluble Group VIIIB metal salts.
[0034] According to some embodiments of the present invention, preferably, the iron salt is selected from ferric chloride and / or ferric sulfate.
[0035] According to some embodiments of the present invention, preferably, the molybdate is selected from sodium molybdate and / or ammonium molybdate.
[0036] According to some embodiments of the present invention, preferably, the cobalt salt is selected from cobalt chloride and / or cobalt nitrate.
[0037] More preferably, the molar ratio of the two metal elements (molybdenum to cobalt, molybdenum to iron, cobalt to iron) in the metal salt is 1:(1-5), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5:1:5, or any value between the above values or a range consisting of any two values. As mentioned above, the two metal elements can be any two of iron, molybdenum and cobalt.
[0038] In the present invention, when the metal salt meets the above range, the metal elements in the metal salt can be more evenly combined on the surface of the biochar, synergistically promoting the generation of active species in the degradation reaction and improving the catalytic performance of the composite material.
[0039] In the present invention, in order to further increase the synthesis reaction rate of the composite material and promote crystal growth, preferably, the promoter is selected from urea and / or thiourea.
[0040] In the present invention, the etchant can mainly extract electrons from the surface of the biochar to produce an etching effect, so as to generate oxygen vacancy defects on the surface of the biochar, further increasing the activity of the composite material. In order to further promote the generation of oxygen vacancy defects on the surface of the biochar, preferably, the etchant includes ammonium fluoride.
[0041] Preferably, based on the dry weight of 10 g of the biomass raw material, the amount of the promoter is 0.05-0.3 mol.
[0042] Preferably, based on the dry weight of 10 g of the biomass raw material, the amount of the etchant used is 0.1-0.4 mol.
[0043] In the present invention, when the promoter and the etchant meet the above ranges, the metal elements in the metal salt can grow more evenly on the surface of the biochar and construct more oxygen vacancies.
[0044] In the present invention, the mixing is preferably carried out in the presence of a solvent (such as water), and the dry matter content of the biomass raw material in the mixing system is 0.04-0.3% by weight.
[0045] In the present invention, the mixing is not particularly limited. For example, the metal salt, promoter, etchant and biomass raw material can be mixed and then dissolved in a solvent. Alternatively, the metal salt, promoter and etchant can be dissolved in a solvent to form a solution, which is then mixed with the biomass raw material.
[0046] In the present invention, there is no particular limitation on the mixing method of the metal salt, promoter and etchant with the biomass raw material. The mixing may be performed once or multiple times. For example, the metal salt solution, promoter solution and etchant solution may be directly mixed with the biomass raw material, or the promoter solution and etchant solution may be first mixed with the biomass raw material and then the metal salt solution may be added for mixing.
[0047] In the present invention, preferably, the mixing is carried out in a reactor, for example, the metal salt solution, the accelerator solution and the etchant solution are mixed with the biomass raw material and then transferred to the reactor for reaction.
[0048] According to some embodiments of the present invention, preferably, the mixing conditions include: temperature of 180-220° C., and time of 15-22 h.
[0049] In the present invention, after the metal salt, promoter and etchant are mixed with the biomass raw material, the method may further include: cooling to room temperature, solid-liquid separation to obtain solid particles, further washing and drying, removing soluble impurities on the surface of the solid particles, and obtaining a pure composite material. Those skilled in the art may select a suitable process as needed (for example, the filtered solid particles may be washed with ethanol and deionized water in turn, 3-5 times), which will not be repeated here. Drying conditions may include: a temperature of 60-90°C and a time of 8-12h.
[0050] In a particularly preferred embodiment of the present invention, the method comprises:
[0051] (1) mixing the invasive herb, an accelerator, an etchant, a metal salt and water, reacting the mixture at 180-220° C. for 15-22 hours, cooling the mixture to room temperature after the reaction, and performing solid-liquid separation to obtain solid particles;
[0052] Wherein, based on the dry matter weight of 10g of the invasive herb, the dosage of the accelerator is 0.05-0.3mol, and the dosage of the etchant is 0.1-0.4mol;
[0053] The cellulose content of invasive herbs is 45-65wt% based on the dry matter weight of invasive herbs;
[0054] The weight ratio of the metal element in the metal salt to the dry matter of the invasive herbaceous plant is 1:(0.5-10);
[0055] The amount of the metal salt used is such that the molar ratio of the iron element to the cobalt element is 1-5:1;
[0056] (2) washing and drying the solid particles to obtain a composite material. The composite material obtained according to this preferred embodiment is rich in oxygen vacancies and has better catalytic performance. It is used for persulfate activation and degradation of organic pollutants and can efficiently remove a variety of organic pollutants in water, with a removal rate of 100% and a mineralization rate of 80%.
[0057] The second aspect of the present invention provides a composite material containing oxygen vacancies, and the composite material is prepared by the method described in the first aspect.
[0058] In a preferred embodiment of the present invention, the composite material includes carbon and two metal elements. As mentioned above, the two metal elements may be any two of iron, molybdenum and cobalt.
[0059] Preferably, the weight ratio of carbon, cobalt and molybdenum elements in the composite material is 6-9:4-6:1.
[0060] Preferably, the weight ratio of carbon, iron and molybdenum elements in the composite material is 7-10:2-4:1.
[0061] Preferably, the weight ratio of carbon, iron and cobalt in the composite material is 6-9:1-3:1.
[0062] The composite material of the present invention is a nanometer to micrometer scale sheet structure and is rich in oxygen vacancies.
[0063] The third aspect of the present invention provides an application of the composite material containing oxygen vacancies described in the second aspect and persulfate in the degradation of organic pollutants.
[0064] In practical applications, the amount of the composite material can be 50-100 mg relative to 10 mg of organic pollutants. The treatment method and conditions are as follows: under visible light irradiation, the composite material and persulfate (such as peroxymonosulfate and / or peroxydisulfate) are added to a water body containing organic pollutants, and after 0.5-60 minutes, the content of organic pollutants in the water body is sampled and detected. Among them, the weight ratio of the composite material to the persulfate is preferably 1: (0.5-2).
[0065] In the present invention, the organic pollutants may be various common organic substances, for example, may include at least one of iohexol, tetracycline, bisphenol A, rhodamine B, ciprofloxacin, and methyl blue.
[0066] Example
[0067] The present invention will be described in detail below through examples.
[0068] In the following examples, unless otherwise specified, all raw materials are commercially available.
[0069] The metal element content and carbon element content in the composite material were determined by inductively coupled plasma mass spectrometry and elemental analyzer, and the instrument models were Agilent 7700x and vario EL cube, respectively.
[0070] The weight of the invasive plants in this embodiment is measured by the weight of the dry powder of the invasive plants. The collected invasive plants need to be pre-processed to obtain the dry powder, as follows:
[0071] Place fresh samples of invasive plants in a constant temperature drying oven, dry at 70°C to constant weight, cool and grind with a grinder for later use.
[0072] Example 1
[0073] This example is used to illustrate the preparation of a composite material using the method described in the present invention.
[0074] (1) 3 mmol of cobalt nitrate, 1 mmol of sodium molybdate, 9 mmol of ammonium fluoride, 4.5 mmol of thiourea and 400 mg of dried sample of Pleurotus eryngii were added to 150 mL of water and mixed to obtain a mixed solution;
[0075] Wherein, based on the dry matter weight of the small grass, the cellulose content in the small grass is 54wt%;
[0076] (2) transferring the mixed solution to a reactor and reacting it at 200° C. for 18 h. After the reaction, cooling it to room temperature and centrifuging to obtain solid particles.
[0077] (3) washing the solid particles with ethanol and deionized water three times in sequence, and drying at 60° C. for 12 h to obtain a composite material S1;
[0078] Wherein, the weight ratio of carbon, cobalt and molybdenum elements in the composite material S1 is 8.6:4.5:1;
[0079] See the appearance photos of the dried sample of Pleurotus eryngii and the composite material S1. Figure 1 The prepared composite material S1 was tested by scanning electron microscopy, transmission electron microscopy and electron spin resonance, and the results were as follows: Figure 2 , Figure 3 and Figure 4 As shown. Figure 2 It can be seen that the molybdenum-cobalt bimetallic elements were successfully loaded on the biochar surface; Figure 3 It can be seen that the composite material S1 is a sheet-like structure; Figure 4 It can be seen that there is a very strong g=2.003 peak in the electron spin resonance image of the composite material S1, indicating that the composite material S1 is rich in oxygen vacancies.
[0080] Example 2
[0081] This example is used to illustrate the preparation of a composite material using the method described in the present invention.
[0082] (1) 3 mmol of ferric chloride, 1.5 mmol of sodium molybdate, 9 mmol of ammonium fluoride, 4.5 mmol of thiourea and 400 mg of Aster tataricus dry sample were added to 150 mL of water and mixed to obtain a mixed solution;
[0083] (2) transferring the mixed solution to a reactor, reacting at 220° C. for 15 h, cooling to room temperature after the reaction, and centrifuging to obtain solid particles;
[0084] Among them, based on the dry matter weight of Aster edulis, the cellulose content in Aster edulis is 61wt%;
[0085] (3) washing the solid particles with ethanol and deionized water three times in sequence, and drying at 70° C. for 8 h to obtain a composite material S2;
[0086] Wherein, the weight ratio of carbon, iron and molybdenum elements in the composite material S2 is 9.0:2.8:1;
[0087] The prepared composite material S2 was tested by scanning electron microscopy and transmission electron microscopy, and the results were as follows: Figure 5 and Figure 6 As shown. Figure 5 It can be seen that the composite material S2 is in the shape of a bouquet, indicating that the loaded metal is well crystallized; Figure 6 It can be seen that the Mo-Fe bimetallic elements are evenly distributed on the surface of biochar.
[0088] In addition, the composite material S2 was subjected to electron spin resonance detection, and the obtained electron spin resonance graph was similar to that of Example 1.
[0089] Example 3
[0090] This example is used to illustrate the preparation of a composite material using the method described in the present invention.
[0091] (1) 3 mmol of ferric sulfate, 1.5 mmol of cobalt nitrate, 9 mmol of ammonium fluoride, 4.5 mmol of thiourea and 400 mg of Alternanthera philoxeroides dry sample were added to 150 mL of water and mixed to obtain a mixed solution;
[0092] (2) transferring the mixed solution to a reactor, reacting at 180° C. for 22 h, cooling to room temperature after the reaction, and centrifuging to obtain solid particles;
[0093] Among them, based on the dry matter weight of Alternanthera philoxeroides, the cellulose content of the invasive plant is 62wt%;
[0094] (3) washing the solid particles with ethanol and deionized water three times in sequence, and drying at 60° C. for 8 h to obtain a composite material S3;
[0095] Wherein, in the composite material S3, the weight ratio of carbon, iron and cobalt elements is 7.4:2.2:1;
[0096] The prepared composite material S3 was tested by transmission electron microscopy. Figure 7 As shown. Figure 7 It can be seen that the iron-cobalt bimetallic elements are evenly distributed on the surface of biochar;
[0097] In addition, the composite material S3 was subjected to scanning electron microscopy and electron spin resonance detection, and the obtained scanning electron microscopy image and electron spin resonance image were similar to those of Example 1.
[0098] Example 4
[0099] A composite material S4 was prepared in the same manner as in Example 1, except that sodium molybdate in step (1) was replaced by cobalt nitrate, and other conditions were the same;
[0100] The prepared composite material S4 was subjected to electron spin resonance detection, and the results were as follows Figure 4 .from Figure 4 It can be seen that the electron spin resonance graph of composite material S4 has a peak of g = 2.003, but the relative intensity is weaker than that of S1, indicating that the number of oxygen vacancies in composite material S4 is less than that in S1;
[0101] In addition, the composite material S4 was subjected to scanning electron microscopy and transmission electron microscopy, and the obtained scanning electron microscopy images and transmission electron microscopy images were similar to those of Example 1.
[0102] Comparative Example 1
[0103] The comparative example is used to illustrate the preparation of composite materials using conventional biomass materials.
[0104] A composite material DS1 was prepared in the same manner as in Example 1, except that corn cobs with a cellulose content of 29% were used in step (1). Other conditions were the same, and composite material DS1 was prepared.
[0105] Comparative Example 2
[0106] The composite material DS2 was prepared in the same manner as in Example 1, except that no etchant and accelerator were added in step (1). The other conditions were the same, and the composite material DS2 was prepared.
[0107] Comparative Example 3
[0108] A composite material DS3 was prepared in the same manner as in Example 1, except that no metal salt was added in step (1). Other conditions were the same, and the composite material DS3 was prepared.
[0109] Test Example 1
[0110] The composite materials and persulfate were added to water bodies containing organic pollutants, and the removal rates and mineralization rates of different types of organic pollutants were measured.
[0111] Determination of organic pollutant content in water: 5 mg of the composite material and 5 mg of potassium permonosulfate were added to 50 mL of water containing organic pollutants (the concentrations of iohexol, tetracycline, bisphenol A, rhodamine B, methyl blue and ciprofloxacin were 10 mg / L respectively). Under visible light irradiation, 0.9 mL of water was taken into a centrifuge tube containing 0.1 mL of methanol every 0.5 min, and the content of different types of organic pollutants in the water was determined according to the following detection method. The determination results are shown in Table 1, and the degradation curve of iohexol is shown in Figure 8-9 .
[0112] Determination of mineralization rate of organic pollutants in water: 5 mg of composite material and 5 mg of potassium permonosulfate were added to 50 mL of water containing organic pollutants (the total concentration of iohexol, tetracycline, bisphenol A, rhodamine B, methyl blue and ciprofloxacin was 40 mg / L), and samples were taken at 0 min and 60 min respectively under visible light irradiation. The total organic carbon in the water was determined according to the following detection method, and the mineralization rate of organic pollutants was calculated according to the following formula. The determination results are shown in Table 1.
[0113] Determination method of iohexol in water: Determination is carried out in accordance with the provisions and test methods of "HJ 778-2015" "Ion Chromatography for Determination of Iodide in Water Quality", and the instrument model is Agilent1290.
[0114] Determination method of tetracycline in water: high performance liquid chromatography, instrument model Agilent1290.
[0115] Determination method of bisphenol A in water bodies: Determination is carried out in accordance with the provisions and test methods of "HJ 1192-2021" "Solid Phase Extraction / High Performance Liquid Chromatography for Determination of 9 Alkylphenol Compounds and Bisphenol A in Water Quality", and the instrument model is Agilent1290.
[0116] Determination method of Rhodamine B in water: UV spectrophotometry, instrument model TU1900.
[0117] Determination method of methylene blue in water: Determination is carried out in accordance with the provisions and test methods of "HJ 1226-2021" "Determination of Sulfide in Water Quality-Methylene Blue Spectrophotometric Method", instrument model TU1900.
[0118] Determination method of ciprofloxacin in water: Ultra high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF) quantitative analysis method is used, and the instrument model is Agilent1290-6530.
[0119] Removal rate of organic pollutants (%) = (amount of pollutants removed / content of organic pollutants in the original water) × 100%.
[0120] Mineralization rate of organic pollutants (%) = (carbon content in carbon dioxide generated in the water body / total organic carbon content in organic pollutants in the original water body) × 100%.
[0121] Method for determination of total organic carbon in water: Determination shall be carried out in accordance with the provisions and test methods of "HJ 501-2009", instrument model is Vario TOC.
[0122] Table 1
[0123]
[0124]
[0125] By comparing the results of the embodiment and the comparative example, it can be seen that when the composite material prepared by the method of the present invention is used for the degradation of organic pollutants in water bodies by the persulfate system, the removal rate of the composite material for iohexol is 100% within 4 minutes, and the mineralization rate of the composite material for organic pollutants is 80% within 60 minutes, thereby achieving efficient and deep removal of multiple organic pollutants in water bodies. When the composite material prepared by the method of the comparative example is used for the degradation of organic pollutants in water bodies by the persulfate system, the removal rate of the composite material for iohexol is only 22% within 4 minutes, and the mineralization rate of the composite material for organic pollutants is only 10% within 60 minutes. It can be seen that compared with the prior art, the composite material of the present invention is used for the catalytic degradation of organic pollutants in water bodies by the persulfate system, and the degradation efficiency is faster and the effect is more excellent.
[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite material containing oxygen vacancies, characterized in that: The method comprises: mixing a metal salt, a biomass raw material, a promoter and an etchant in the presence of a solvent to carbonize the biomass raw material; Wherein, the biomass raw materials are derived from invasive plants.
2. The preparation method according to claim 1, wherein The weight ratio of the metal element in the metal salt to the dry matter of the biomass raw material is 1:(0.5-10).
3. The preparation method according to claim 1 or 2, wherein The invasive plants are selected from the genus Erigeron and / or the genus Aster in the family Asteraceae; Preferably, the invasive plant is selected from at least one of Aster philadelphica, Aster philadelphica and Alternanthera philadelphica.
4. The preparation method according to claim 3, wherein Based on the dry matter weight of the invasive plant, the cellulose content in the invasive plant is 45-65wt%.
5. The preparation method according to claim 1 or 2, wherein: The metal salt is selected from at least one of transition metal salts; Preferably, the transition metal salt is selected from any two of iron salts, molybdates, cobalt salts, copper salts and manganese salts; More preferably, the transition metal salt is selected from any two of iron salts, molybdates and cobalt salts.
6. The preparation method according to claim 5, wherein: The iron salt is selected from ferric chloride and / or ferric sulfate; And / or, the molybdate is selected from sodium molybdate and / or ammonium molybdate; And / or, the cobalt salt is selected from cobalt chloride and / or cobalt nitrate.
7. The preparation method according to claim 5, wherein: The molar ratio of the two metal elements in the metal salt is 1:(1-5).
8. The preparation method according to claim 1, wherein Based on the dry weight of 10g of the biomass raw material, the amount of the promoter is 0.05-0.3mol, and the amount of the etchant is 0.1-0.4mol; and / or, the accelerator is selected from urea and / or thiourea; and / or, the etchant comprises ammonium fluoride; and / or, the solvent is water; Preferably, the mixing conditions include: temperature of 180-220° C. and time of 15-22 h.
9. A composite material containing oxygen vacancies, characterized in that: The composite material is prepared by the method described in any one of claims 1 to 8.
10. Use of the composite material according to claim 9 and persulfate in degrading organic pollutants.
